Triggering and Relationship Between Mine Earthquake Activities and Stress of Earth Tides During Deep Mining - Zhang, Yuezheng; Ji, Hongguang; Wu, Haoyuan (Frontiers in Earth Science, 2022)
In the process of deep mining, the prevention and control of rock bursts, mine earthquakes, and other disasters are common problems. The stress of earth tides and its periodic actions should trigger mine earthquakes when the rock masses are in a critical state of rupture. In this study, the Yanbei coal mine was taken as the research background to explore the triggering effect of solid tides on mine earthquakes occurring in the floor. The relationship between the diurnal tidal stress phase and mine earthquakes was studied by statistically analyzing the mine earthquake frequency, and the triggering mechanism was also preliminarily discussed. It was found that the solid tide plays a significant role of trigger action in the occurrence of rock burst of the floor type. For different levels of mine earthquakes, the tidal stress triggering effect is different, but the overall trend is close. Compared with the components of tidal stress, vertical stress, north-south stress, and shear stress, rock burst occurred more at the stage close to 0° and ±180°. For different types of mine earthquakes, the triggered mechanics function of tidal stress is different. Mine earthquakes on the floor mainly include two kinds (the gravity control type and horizontal stress control type). The former easily occurs during the tidal stress vertical component of the maximum, while the latter easily occurs when the two horizontal components of the maximum are combined. The frequency of the former is larger than that of the latter. The results show that the floor seismic activity is correlated with the solid tidal activity of the earth’s crust, which provides a new idea for understanding the mechanism and trigger conditions of mine earthquakes.